Investigation of Some Physical and Mechanical Properties of Basalt Fiber-Reinforced Polymer (BFRP) Woven Fabrics and Plaster Mesh (PSM) Reinforced Glued Laminated Oak Lumber - Abdurrahman Karaman; Huseyin Yesil (Drvna Industrija)
In this study, some physical and mechanical properties of the basalt fiber-reinforced polymer (BFRP) woven fabrics (WF) and plaster mesh (PSM) reinforced glued laminated oak lumber were investigated. The BFRPWF and PSM were used in order to increase the mechanical properties of the laminated elements. One-component polyurethane glue (PUR) was used in the production of lumber. The BFRPWF and PSM were tested in three different locations using non-reinforced laminated oak lumber (LOL), reinforced laminated oak lumber with BFRPWF (LOLBFRPWF), and reinforced laminated oak lumber with PSM (LOL-PSM). Tests were performed on the LOL, LOLBFRPWF, and LOL-PSM to investigate their bending strength (MOR), air-dried density (δ12), and modulus of elasticity (MOE). The three-point MOR and MOE in bending tests were applied to the samples. The results showed that the highest value for MOR was found in the laminated wood samples (135.20 N/mm2) that were prepared using the BFRPWF inter-layer. The lowest value of 112.82 N/mm2 was found in the LOL samples. The highest value of modulus elasticity was found in the samples prepared with the BFRPWF inter-layer (16167 N/mm2). The lowest value of 13786 N/mm2 was found in the LOL samples. It was observed that the samples parallel to the glue line of the laminated material showed higher performance compared to those perpendicular to the glue line. The LOL-BFRPWF samples give better results than LOL-PSM and control samples. Accordingly, the LOL-BFRPWF and LOL-PSM samples have the potential to be used as viable options for both furniture and building materials.